A Proposed Analytical Inter-Cell Interference Model for Mobile Cellular Systems with Isotropic Antenna - Abdalqadir, Raz Shara; Ameen, Araz Sabir (Sulaimani Journal for Engineering Sciences, 2023)
4G and beyond cellular systems intend to use a frequency reuse factor of one with three sectors per BS site. This configuration leads to an increase in inter-cell interference (ICI). Thus, ICI modeling is very necessary to design and analyze any cellular system. The impact of ICI is modeled analytically in this paper. The effect of six interfering BS sites surrounding the serving BS is examined. The ICI is first mathematically modeled as a function of BS-UE distance for several environments based on pathloss exponent and then validated using an explicit simulation model. Secondly, the results obtained from the proposed model and the explicit simulation model are compared. The comparisons showed good agreement between the results of the proposed model and the simulation model. The mathematical model is convenient to the standardized ITU-R model and has the flexibility to apply any antenna patterns that is compatible with these international models. Furthermore, this model enables ICI estimation by deploying the serving BS cell only without the need to deploy the surrounding nine interfering cell. This has positive impact on reducing the time required for system level simulation.
Keywords: Cellular systems; inter-cell interference; interference modeling